Exploring the Relationship Between Job Satisfaction and Work Engagement Among Generation Z Employees - Yulia Fitriani; Zhika Nur Cahyani; Fathana Gina (Journal of Islamic Psychology and Behavioral Sciences, 2026)
Generation Z is a workforce group that is currently beginning to dominate the workplace and exhibits characteristics that differ from previous generations, making work engagement an important aspect to consider. One factor believed to be associated with work engagement is job satisfaction. This study aims to examine the relationship between job satisfaction and work engagement among Generation Z. The study employs a quantitative approach with a correlational design. The sample consists of 101 Generation Z employees selected using convenience sampling. Data collection utilized job satisfaction and work engagement scales that met validity and reliability criteria. Data analysis was performed using Pearson’s Product-Moment correlation. The results indicate a positive and significant relationship between job satisfaction and work engagement among Generation Z, with a correlation coefficient of 0.582 and a significance level of less than 0.001. These findings suggest that the higher an individual’s perceived job satisfaction, the higher their work engagement. These findings underscore the importance of job satisfaction as a key factor in enhancing work engagement among Generation Z.